Um cenário de educação linguística crítica, integral e humanizadora na infância com texturas da Pedagogia Waldorf - Lorenzoni, Carla Raqueli Navas (Universidade Federal de São Carlos, 2022)
This research is related to the experiences (DEWEY, 1979) of additional language teachers in the initial years of schools that follow the Waldorf Pedagogy (STEINER, 1995, 2003, 2015 among others), which is based on a broad and complete view of the human being and his development; from this point of view, children and young people are considered in their individual aspects and in the particularities of the age group to which they belong. The theoretical contribution of this thesis is anchored in the definitions of critical linguistic education (MONTE MÓR, et al., 2018; SABOTA, 2021; FERRAZ, 2015, 2018, 2019), integral education, humanizing education (MORIN, 2017; MOLL, 2019; GUERRA, 2019; GUARÁ, 2006) and transdisciplinar education (LEFFA, 2006; MORIN, 2017) and Waldorf Pedagogy (STEINER, 1995, 2003, 2015; KÜGELGEN, 1984; KIERSCH, 2015; SELG, 2020). The general objective of the research is to report and critically interpret the proposal for language education in Waldorf Pedagogy based on experiences shared by additional language teachers working in schools that follow this pedagogy. The specific objectives are: 1. to investigate and evaluate possible developments of aspects of critical linguistic education and the panorama of additional languages in Waldorf Pedagogy that complement each other and 2. to identify aspects conducive to the critical, integral and humanizing formation of the student in additional language classes from the experiences shared by the teachers/participants. The research methodology that guides the study is the Narrative Research (CLANDININ and CONNELLY, 2011; MELLO, 2004), which directed being in the field, the composition of meanings from field texts and also the emergence of research texts. There were two teachers/participants who shared their experiences of working in the classroom. From these experiences, themes such as transdisciplinarity, ludicity, learning assessment, the integral formation of the student and the humanization of education emerged. With the discussions made from the research texts, it is noted that there is, in additional language classes of Waldorf Pedagogy, the experience of critical linguistic education: the performance of the teachers/participants denotes a work based on the construction of meanings, on the contextualization, respect for the affective character of being, lovingness, dialogue with students. Such action excels in student’s critical, comprehensive and humanizing education.

Esta investigación se relaciona con las experiencias (DEWEY, 1979) de dos profesoras de idiomas adicionales en los años iniciales de escuelas que siguen la Pedagogía Waldorf (STEINER, 1995, 2003, 2015 entre otros), la cual se basa en una visión amplia y completa del ser humano y su desarrollo. Desde este punto de vista, los niños y jóvenes son considerados en sus aspectos individuales y en las particularidades del grupo de edad al que pertenecen. El aporte teórico de esta tesis se ancla en las definiciones de educación lingüística crítica (MONTE MÓR, et al., 2018; SABOTA, 2021; FERRAZ, 2015, 2018, 2019), educación integral, humanizadora (MORIN, 2017; MOLL, 2019; GUERRA, 2019; GUARÁ, 2006) y transdisciplinar (LEFFA, 2006; MORIN, 2017) y Pedagogía Waldorf (STEINER, 1995, 2003, 2015; KÜGELGEN, 1984; KIERSCH, 2015; SELG, 2020). El objetivo general de la investigación es relatar e interpretar críticamente la propuesta de enseñanza de idiomas en la Pedagogía Waldorf a partir de experiencias compartidas por docentes de idiomas adicionales que trabajan en escuelas que siguen esta pedagogía. Los objetivos específicos son: 1. investigar y evaluar posibles desarrollos de aspectos de la educación lingüística crítica y del panorama de lenguas adicionales en la Pedagogía Waldorf que se complementan e 2. identificar aspectos propicios para la formación crítica, integral y humanizadora del estudiante en clases de idiomas a partir de las experiencias compartidas por las docentes/participantes. La metodología de investigación que orienta el estudio es la Investigación Narrativa (CLANDININ y CONNELLY, 2011; MELLO, 2004), que orientó el estar en el campo, la composición de significados a partir de los textos de campo y también la emergencia de los textos de investigación. De las experiencias compartidas surgieron temas como la transdisciplinariedad, la ludicidad, la evaluación del aprendizaje, la formación integral del alumno y la humanización de la educación. Con las discusiones realizadas a partir de los textos de investigación, se constata que existe, en estas clases de lengua adicional de la Pedagogía Waldorf, la experiencia de la educación lingüística crítica: la actuación de las docentes/participantes denota un trabajo basado en la construcción de significados, en la contextualización, en el respeto por el carácter afectivo del ser, en el cariño y en el diálogo con los alumnos. Tal acción se destaca por la formación crítica, integral y humanizadora del educando.
A scenario of critical, integral and humanizing linguistic education in childhood with textures from Waldorf Pedagogy
Keywords: Educação linguística crítica; Pedagogia Waldorf; Infância; Formação integral e humanizadora; Pesquisa narrativa; Critical linguistic education; Waldorf Pedagogy; Childhood; Narrative Research; Educación lingüística crítica; Pedagogía Waldorf; Niñez; Investigación narrativa; Formación integral y humanizadora; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA